Geographical Information System distribution of health insurance and employment administrator office. Issue 3 (March 2021) - Fitriani, L; Nugraha, M A; Satria, E; Tresnawati, D
Abstract: Social Insurance is currently one of the needs that must be prioritized both for government agencies or companies. Health Insurance and Employment Administrator Office established so that workers or companies get social Insurance services for workers. The purpose of making this article is to be able to assist users in finding Health Insurance and Employment Administrator Office information. At the same time, Health Insurance and Employment Administrator Office employees manage office data and registered companies and target companies (non-participants). The method used in this study is the Rational Unified Process, starting from the inception stage to the construction stage. The result of this research is the model application of the distribution of the West Java Health Insurance and Employment Administrator Office by adopting Google maps as a provider of information in the form of graphs. With this model expected, the attractiveness of registering and managing social Insurance for workers will increase.